Thromboxane Prostanoid Receptors Enhance Contractions, Endothelin-1, and Oxidative Stress in Microvessels From Mice With Chronic Kidney Disease. Issue 5 (May 2015) - Wang, Cheng; Luo, Zaiming; Kohan, Donald; Wellstein, Anton; Jose, Pedro A.; Welch, William J.; Wilcox, Christopher S.; Wang, Dan
Abstract : Cardiovascular disease is frequent in chronic kidney disease and has been related to angiotensin II, endothelin-1 (ET-1), thromboxane A2, and reactive oxygen species (ROS). Because activation of thromboxane prostanoid receptors (TP-Rs) can generate ROS, which can generate ET-1, we tested the hypothesis that chronic kidney disease induces cyclooxygenase-2 whose products activate TP-Rs to enhance ET-1 and ROS generation and contractions. Mesenteric resistance arterioles were isolated from C57/BL6 or TP-R+/+ and TP-R−/− mice 3 months after SHAM-operation (SHAM) or surgical reduced renal mass (RRM, n=6/group). Microvascular contractions were studied on a wire myograph. Cellular (ethidium: dihydroethidium) and mitochondrial (mitoSOX) ROS were measured by fluorescence microscopy. Mice with RRM had increased excretion of markers of oxidative stress, thromboxane, and microalbumin; increased plasma ET-1; and increased microvascular expression of p22 phox, cyclooxygenase-2, TP-Rs, preproendothelin and endothelin-A receptors, and increased arteriolar remodeling. They had increased contractions to U-46, 619 (118±3 versus 87±6, P <0.05) and ET-1 (108±5 versus 89±4, P <0.05), which were dependent on cellular and mitochondrial ROS, cyclooxygenase-2, and TP-Rs. RRM doubled the ET-1-induced cellular and mitochondrial ROS generation ( P <0.05). TP-R−/− mice with RRM lacked these abnormal structural and functional microvascular responses and lacked the increased systemic and the increased microvascular oxidative stress and circulating ET-1. In conclusion, RRM leads to microvascular remodeling and enhanced ET-1-induced cellular and mitochondrial ROS and contractions that are mediated by cyclooxygenase-2 products activating TP-Rs. Thus, TP-Rs can be upstream from enhanced ROS, ET-1, microvascular remodeling, and contractility and may thereby coordinate vascular dysfunction in chronic kidney disease. Abstract : Supplemental Digital Content is available in the text.